Community-Centric Programs implemented by the Polytechnic University of the Philippines: Leading to Sustainability and Community Development - Salorsano, Glenda; Llames, Jackson Jake; Dino, Roan Jessa (International Journal of Psychosocial Rehabilitation, 2020)
The Community Development in Southeast Asia has been explored and adapted into a locally approach to analyze the dynamics of concept, organization, system and grass-root economic status within different groups in the region. This has been initially developed within the last thirty years and still developing. (The World Bank, 2009)  In the case of Philippines, the academe either, Private or State University is playing a big role as conduit to transfer such technology and knowledge for the development of one community. Academe extends services and implements programs for sustainability of the identified groups and community. (Zuberr-Skerritt, 2012)  This study focused on the Perception of the selected Community in the Programs Implemented by the Polytechnic University of the Philippines, the country’s largest State University in terms of population, which leads to sustainability and community development. It aims to identify and to assess the perception of the selected communities in the programs implemented by PUP which solely focused on Literacy (Basic and Advance Correspondence for the Barangay), Livelihood (Meat and Fish Processing) and Environmental Awareness (Urban Gardening and Waste Segregation, Techniques, Treatment and Disposal Technologies) and how these programs contribute to the development of the communities. Also, this study will show the impacts of the continuous implementation of the programs that wrap up into economical attribute (in the case of literacy and livelihood) and environmental sustainability which lead to community development. The study used a validated survey-questionnaire to evaluate the perception of different respondents coming from District 6 of Metro Manila which where the Polytechnic University of the Philippines is located. Also, an interview was conducted to supplement the information gathered.